LOWER PLIOCENE BARNACLE FACIES OF WESTERN LIGURIA (NW ITALY): A PEEK INTO A WARM PAST AND A GLIMPSE OF OUR INCOMING FUTURE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2021)
The lower Pliocene deposits of Pairola (Liguria, Italy) display the otherwise rare occurrence of rock-forming amounts of barnacles (mostly belonging to the extinct Euromediterranean species Concavus concavus). Three main facies are recognised in the investigated succession: a barnacle-dominated facies, which formed along a shallow (
Keywords: climate change; barnamol; Concavus; Zanclean; Amphistegina; siliciclastic-carbonate deposits